INCREASING STUDENTS’ ENGAGEMENT AND ACADEMIC ACHIEVEMENT THROUGH THE INTEGRATION OF PROBLEM-BASED LEARNING AND DIFFERENTIATED INSTRUCTION MODELS AT SMA NEGERI 6 KABUPATEN LAMPUNG TIMUR - Septi, Septia Uswatun Hasanah; Muhammad Zajuli (JETA (Journal of English Teaching and Applied Linguistic), 2025)
Education plays a vital role in shaping excellent and adaptive human resources, which are the foundation of national development. However, the low interest and academic achievement of students—particularly in the subject of Indonesian language—remain a prevalent issue. One contributing factor is the use of outdated and less innovative teaching methods that do not meet students’ needs. This study aims to improve student engagement and academic achievement through the integration of differentiated instruction within a Problem-Based Learning (PBL) model, focusing on news text material. The research method used was classroom action research (CAR) based on the Kemmis and McTaggart model, implemented in two cycles. The research subjects were 36 eleventh-grade students at SMA Negeri 6 in East Lampung Regency. Data collection techniques included tests, observation, and documentation. The results showed an increase in learning engagement from 67% in the pre-cycle to 78% in cycle I, and 84% in cycle II. Meanwhile, academic mastery increased from 56% to 69%, and then to 89% across the same phases. These findings indicate that integrating differentiated instruction into the PBL model has a positive impact on the quality of Indonesian language learning.